Problems and solutions in the development of the economy of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the indicators of economic development of Uzbekistan. Today, the problems and shortcomings in the development of the economy of Uzbekistan have been deeply analyzed, and the experience of foreign countries has been studied.